2012
DOI: 10.3934/mbe.2012.9.61
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of dynamic outlet boundary conditions in a 1D fluid dynamics model

Abstract: When modeling the cardiovascular system, the use of boundary conditions that closely represent the interaction between the region of interest and the surrounding vessels and organs will result in more accurate predictions. An often overlooked feature of outlet boundary conditions is the dynamics associated with regulation of the distribution of pressure and flow. This study implements a dynamic impedance outlet boundary condition in a one-dimensional fluid dynamics model using the pulmonary vasculature and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This suggests that the overall compliance does not differ significantly between the pulmonary arterial and venous trees. Consequently, we use a constant compliance Ehr0=195normalmnormalmnormalHnormalgfalse(26normalknormalPnormalafalse), approximately the same value used by Clipp & Steele (2009, 2012), for both pulmonary arteries and veins. This value gives simulated pressure waveforms consistent with the physiological ranges of 8.8 ± 3.3–22 ± 4.2 mmHg (Greenfield & Douglas, 1963; Herve et al , 1989), 10–25 mmHg (Fung, 1996) and 8–25 mmHg (Hall, 2011) in the proximal pulmonary arteries.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the overall compliance does not differ significantly between the pulmonary arterial and venous trees. Consequently, we use a constant compliance Ehr0=195normalmnormalmnormalHnormalgfalse(26normalknormalPnormalafalse), approximately the same value used by Clipp & Steele (2009, 2012), for both pulmonary arteries and veins. This value gives simulated pressure waveforms consistent with the physiological ranges of 8.8 ± 3.3–22 ± 4.2 mmHg (Greenfield & Douglas, 1963; Herve et al , 1989), 10–25 mmHg (Fung, 1996) and 8–25 mmHg (Hall, 2011) in the proximal pulmonary arteries.…”
Section: Methodsmentioning
confidence: 99%
“…effects of the respiratory cycle). These are well known [6] and should be contained within the uncertainty bounds of the model. Figure 5.…”
Section: Importance Of Correcting For Model Mismatchmentioning
confidence: 99%
“…Several previous studies [3][4][5][6][7] have developed 1D fluiddynamics models predicting pulmonary blood flow and pressure. However, only a few [3,4] have aimed at devising subject-specific predictions by estimating model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of outflow boundary conditions have been used in the previous works, including the constant resistance model (CR) [ 18 21 ], the tapering-vessel model [ 22 ], the Windkessel model (WK) [ 6 , 23 – 26 ], and the structured tree model (ST) [ 17 , 27 30 ]. In a number of specialized applications, a non-constant resistance model has been used to model the effect of cerebral autoregulation in the brain [ 31 ], and a structured tree model incorporating the effects of geometry, compliance, and respiration has been used to mimic the pulmonary vascular system [ 32 , 33 ]. It has also been reported that outflow boundary conditions can greatly affect the wave profile in the upstream arteries [ 11 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impedance of a structured tree, which is the ratio of the Fourier coefficient of the blood pressure to that of the flow rate at the inlet of the structured tree, is obtained from the linearized system of the one-dimensional model of blood flow in the structured tree. With the ST model, detailed characteristics of the pulse wave such as the dicrotic wave are observed in the simulations [ 11 , 29 , 30 , 32 , 33 ]. Therefore, it is important to carry out a systematic comparison among these models.…”
Section: Introductionmentioning
confidence: 99%